PENERAPAN MEDIA APLIKASI GEOGEBRA DALAM PEMBELAJARAN MATERI BANGUN RUANG SISI DATAR - Grafi Lonto; James U. L. Mangobi; Marvel G. Maukar (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study was to determine the difference in the average learning outcomes of flat building materials of students taught using Geogebra applications and without Geogebra application Media. This study is an experimental study, with a post-test-only control design. The subjects in this study are Class VIII-A as a media experiment class applied to Geogebra application and VIII-B as a control class without the application of GeoGebra application media, both classes are homogeneous and equal to 20 students. The data of this study are taken from the results of the second post-test class. The mean value of the experimental class posttest is 75.3 and the mean value of the control class posttest is 69.2. The results obtained on the basis of hypothesis tests using a T-test with a significance level of 5% obtained value = 2,396793 > = 1,68595, and then reject . Thus, it can be concluded that the learning outcomes of students applying Geogebra application Media are more than the learning outcomes of students without applying Geogebra application Media